Postmodern necrologies. Vanguardism, cyberculture and interactive mutations - Ojeda, Rafael (2022)
The emergence of the avant-garde ended up affecting the categories that until then had served to satisfactorily interpret a multiplicity of phenomena that resulted in unstable and chaotic fluctuations, and determined qualitative changes in the so- cio-cultural structures of the planet, transformations that will have quantitative repercussions in the arts and historical culture. In this context, the idea that post- modernity succeeds modernity is somewhat complicated, due to the resistance of a certain intellectual sector in terms of validation and invalidation of the concept. Nevertheless, the factuality of elements that refer to a new symbolic-practical or- der, which in the arts associated with ICT gave rise to interactive “avant-gardes”, deojectualized and delocalized in a neo- or post-avant-garde spectrum, in which the electronic and biotec edial art, ended up assuming a partial protagonism.